Metabolic nephropathy in children: gender features of oxalate excretion, relationship with oxidative stress severity and antioxidant defense system - N.R. Aib (Zaslavsky O.Yu., 2019)
Background. The purpose was to investigate gender features of oxalate excretion in metabolic nephropathy, the state of oxidative stress and antioxidant system, depending on oxalate excretion. Material and methods. One hundred seventy-six children with oxalate nephropathy and 84 healthy children were included in the study. Clinical, instrumental and laboratory methods were used. The level of lipid peroxidation (diene conjugates, malondialdehyde) and antioxidant protection enzyme (redox glutathione, glutathione peroxidase and serum catalase), and peroxidation of proteins (neutral and basic aldehyde and ketone derivatives of dinitrophenylhydrazone) were evaluated. Results. The level of oxalate excretion and oxalate/creatinine ratio in the first void urine of patients with metabolic nephropathy was significantly higher vs. control group (p < 0.05). The absolute risk of high and moderate oxalate excretion in girls was 62.0 % higher than that of boys (p < 0.05). The moderate and high oxalate/creatinine ratio was found in 57.0 % of girls and in 27.0 % of boys. Low levels of creatinine excretion and oxalate/creatinine ratio were detected in male patients (p < 0.05). All patients with metabolic nephropathy had significantly increased level of neutral aldehyde and ketone derivatives (p < 0.05) compared to control group. The level of basic aldehyde and ketone derivatives was significantly increased compared to controls in moderate and high oxalate excretion (p < 0.05). Moderate and severe oxalaturia in children with metabolic nephropathy was associated with a decreased plasma and erythrocytic malondialdehyde level compared to control group with mild oxalaturia (p1 < 0.05). In patients with metabolic nephropathy, the activation of the lipid peroxidation was accompanied by a significant decrease in superoxide dismutase, increased activity of catalase and glutathione peroxidase vs. control group (p < 0.05). Conclusions. There is gender dependence between the level of oxalate excretion in metabolic nephropathy; the state of oxidative stress and the system of peroxide oxidation depends on the intensity of first void urinary excretion of oxalates.